Readiness of the Public Junior High Schools in the Province of Albay Offering Robotics: An Assessment - Llabore, Delfin John (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the readiness of public junior high schools in the Province of Albay to offer robotics education, focusing on institutional capacity, challenges, and opportunities within STEM implementation. Anchored on the Triangular Theory of Creativity (Sternberg, 2024), Multidimensional Digital Pedagogy Readiness Theory (Fatma, Fahmi, & Darmawan, 2025), Unified Theory of AI Adoption, and the ROBO GEAR UP framework (Llabore, 2026), the study employed a mixed method research design integrating quantitative and qualitative approaches. Data were collected through structured survey questionnaires and interviews from fifty-six (56) department heads and creative technology teachers across fourteen public junior high schools using total enumeration. Descriptive statistics, including weighted mean and percentage distribution, and thematic analysis were utilized. Findings revealed a significant disparity between funded and non-funded schools. Funded schools demonstrated moderate to high readiness across teachers, facilities, instructional materials, training, and financial resources, while non-funded schools were largely unready due to insufficient training, limited infrastructure, lack of standardized materials, and inadequate funding. Challenges were strongly evident in non-funded schools, whereas funded schools reported minimal constraints. Non-funded schools relied on adaptive strategies such as community support, improvisation, and use of free digital tools, though these approaches raised sustainability concerns. Despite these limitations, robotics education presented opportunities for enhancing technical skills, creativity, engagement, and career readiness. The study concludes that sustainable robotics integration requires alignment of institutional capacity, technical expertise, and financial support, and recommends institutionalized training, improved infrastructure, standardized materials, and sustainable funding mechanisms. The study aligns with SDG 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), and SDG 17 (Partnerships for the Goals), as it promotes equitable access to STEM education, innovation, and collaborative resource mobilization. It contributes to educational, socio-economic, and institutional sustainability by supporting inclusive STEM development, strengthening workforce readiness, and informing policy and program improvement in public schools.
Keywords: Educational Robotics; Financial Resources; Instructional Materials; Public Junior High Schools; Readiness; STEM Education; Teacher Readiness; Training